Neostigmine for non-mild acute pancreatitis: A systematic review and meta-analysis of randomized controlled trials - He, Kun; Wang, Yabing; Li, Jianing; Bai, Xiaoyin; Yang, Zihan; Han, Xianlin; Wu, Dong (Frontiers in Pharmacology, 2023)
Background: The therapeutic value of neostigmine as a prokinetic drug in acute pancreatitis (AP) especially in non-mild AP including moderately severe and severe AP remains controversial. This meta-analysis aimed to investigate the efficacy of neostigmine treatment in patients with non-mild AP. Methods: We searched Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, China National Knowledge Infrastructure (CNKI), WanFang database up to 5th December 2022 for RCTs comparing neostigmine plus conventional treatment versus conventional treatment alone in non-mild AP. Trial sequential analysis (TSA) were used to assess the risk of random errors and assess the results. Results: Six RCTs with 318 participants were included. Compared with conventional treatment, Patients who received neostigmine plus conventional treatment had shorter time to first defecation (MD -1.74, 95% CI -2.10 to -1.38; P＜0.00001; n=205; RCTs=4; low-quality of evidence) and better relief time of abdominal symptoms (MD -1.59, 95% CI -2.07 to -1.11; P＜0.00001; n=155; RCTs =3; low quality of evidence) as primary outcomes, as well as faster percent decrease of IAP at 24h (P=0.0005; moderate-quality of evidence) and shorter length of ICU stay (P < 0.00001; moderate-quality of evidence) as partial secondary outcomes. TSA suggested the sample size was limited but the cumulative Z curves of the primary outcomes crossed the conventional boundary and the trial sequential monitoring boundary. Conclusions: For patients with non-mild AP, neostigmine promotes recovery of gastrointestinal motility and may have positive effect on improvement of clinical prognosis. Further large-sample studies were needed for definite conclusion.